Determinación del potencial de captura de carbono de las especies forestales de aliso (Alnus acuminata) y eucalipto (Eucalyptus globulus) en la localidad de Florida Pomacochas - Villacis Del Castillo, José Tito (2012)
This present research was conducted in Florida Pomacochas town, Bongara province, Amazonas department, Peru, with the overall objective to determine the sequestration potential carbon in forest species as "Aliso;; and "Eucalipto u, as well as having specific objectives as follows: • Make an inventory of the two biometric forest species existing in the sector of study. • To evaluate the quantity of carbon accumulated by every species. • Determine the environmental service of the two forest species present in the study area. All of this in the framework of the project of afforestation and reforestation of the Andean High Andean Basins and Buffer, belong to Alto lmaza, Bongará and Chachapoyas provinces, Amazonas region (PRAl projects). Field activities were: the delimitation of the study area, estimates and pick up biometric samples of litter. These data allowed in cabinet, through the use of allometric formulas, estímate the following results: 3. In Eucalyptus globulus parcel determined 26.29 Tnlha oftotal biomass ofliving trees, moreover 24.14 Tnlha of biomass from litter, these values together with was the amount of 50.43 Tnlha of total plant biomass, this converted to biomass plant carbon introduced 22.69 Tnlha. 4. In Alnusa caminata parcel was estimated 12.69 Tnlha of total biomass of living trees, it also secured 2040 Tnlha of biomass of the litter, coupled with these values was 33.09 Tnlha of total plant biomass, which when converted to biomass plant carbon introduced 14.89 Tn/ha. The obtained results were in parcels of 2500 m2 for species, with plantations of 3 years and 3 months of age. Key words: Eucalipto, carbon accumulated.